Synthesis and biological evaluation of 12-, 13-, 14-membered macrolides and open chain 2, 6-trans-disubstituted dihydropyran analogues for aspergillides. Issue 26 (27th June 2018) - Pabbaraja, Srihari; Gantasala, Naresh; Ydhyam, Sridhar; Namballa, Hari Krishna; Gundeboina, Subhashini; Lambu, Mallikharjuna R.; Meena, Sanjeev; Datta, Dipak
Graphical abstract: Highlights: Synthesis of several analogue compounds for aspergillides was accomplished. Twenty macrolides have been synthesized. Seventeen open-chain 2, 6- trans -disubstituted dihydropyran derivatives synthesized. One compound was found to display anticancer properties. Abstract: Stereoselective synthesis of twenty (three 12-, five 13- and twelve 14-membered) macrolides and seventeen functionalized 2, 6- trans -disubstituted dihydropyran derivatives have been achieved. The key reactions include an Achmatowicz rearrangement, Ferrier-type alkynylation, Yamaguchi macrolactonization and Lindlar's hydrogenation. Biological screening of the synthesised compounds showed moderate activity against human cancer cell-lines.